2017
DOI: 10.1039/c7ta03432f
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of three-dimensional graphene aerogel encapsulated n-octadecane for enhancing phase-change behavior and thermal conductivity

Abstract: Novel 3D-GA composite PCMs were successfully prepared for enhancing the thermal conductivity, energy storage capacity and thermal repeatability of PCMs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(34 citation statements)
references
References 37 publications
2
32
0
Order By: Relevance
“…Since there is no similar study, comparing the outcomes of the current work for the nanocomposite was difficult. The results of this study, as shown in Table 2, aligned well with those outlined in prior works, 10,[29][30][31][32][33] and the simulations conducted in this work could be appropriately validated.…”
Section: Validationsupporting
confidence: 86%
“…Since there is no similar study, comparing the outcomes of the current work for the nanocomposite was difficult. The results of this study, as shown in Table 2, aligned well with those outlined in prior works, 10,[29][30][31][32][33] and the simulations conducted in this work could be appropriately validated.…”
Section: Validationsupporting
confidence: 86%
“…On the other hand, three-dimensional (3D) graphene nanostructures composed of 2D graphene sheets have been intensively studied in energy storage [33][34][35], environmental remediation [36][37][38], and gas sensing [39][40][41]. Compared with 2D graphene counterparts, 3D graphene nanostructures can hold interconnected networks with more surface areas and active sites in addition to hierarchical frameworks, which make them an ideal scaffold to inhibit the aggregation or stacking of subunits [42][43][44][45][46]. Further, doping heteroatoms like N into 3D graphene may significantly modify the electronic structure as well as benefit the intimate contact between graphene with dissimilar materials [47][48][49][50].…”
Section: Introductionmentioning
confidence: 99%
“…Although the composite can exhibit shape‐stabilized performance, the thermal conductivity improvement as well as PCM loading capacity is still a challenge. Consequently, introducing PCM into high thermal conductive matrixes including metal oxides, graphene aerogel, carbon nanotube (CNT), expanded vermiculite, metal nanoparticles graphite foam, EG have been reported to improve the thermal conductivity of composite PCMs. For example, with increased functionalized multi‐walled carbon nanotubes content, the thermal conductivity of paraffin/f‐MWCNTs composite PCMs showed significant improvement up to 0.53 W/mK without leakage .…”
Section: Introductionmentioning
confidence: 99%